Stewardship of the Aged: Meeting the Ethical Challenge of Ageism - Thomasma, David C. (Cambridge quarterly of healthcare ethics, 1999)
Medical ethics is a footnote to the larger problem of directing our technology to good human ends. Written large, then, medical ethics must ask five basic questions:1)Is it even possible to direct biomedical technology to good human ends, or is the medical enterprise almost entirely technology driven?2)If it is possible to direct biomedical technology, on what basis or norms should this direction take place?3)How should decisionmaking in this control over biomedical technology be structured?4)Who should be involved in the process of making those decisions, and of those involved, whose values and opinions ought to carry more weight?5)Based on the answers to these four questions, what ought to be our concern for the future of medicine?